Evaluation of Protective Effects of Curcumin and Nanocurcumin on Aluminium Phosphide‑Induced Subacute Lung Injury in Rats: Modulation of Oxidative Stress through SIRT1/FOXO3 Signalling Pathway - Mahlooji, Mohammad Ali; Heshmati, Ali; Kheiripour, Nejat; Ghasemi, Hassan; Asl, Sara Soleimani; Solgi, Ghasem; Ranjbar, Akram; Hosseini, Asieh (Drug Research, 2021)
Objective Aluminum phosphide (AlP) is widely used to protect stored food products and grains from pests and rodents. The availability of AlP, especially in Asian countries it has become a desirable factor to commit suicide. The phosphine produced from ALP is a very reactive radical and a respiratory inhibitor that causes oxidative damage. There is no dedicated antidote or effective drug to manage AlP-induced lung toxicity. The present study aims to evaluate and compare the protective effects of curcumin and nanocurcumin on ALP‑induced subacute lung injury and determine the underlying mechanism.Methods Rats were exposed to AlP (2 mg/kg/day, orally)+curcumin or nanocurcumin (100 mg/kg/day, orally) for 7 days. Then rats were anesthetized and lung tissues were collected. Oxidative stress biomarkers, genes expression of antioxidant enzymes, participated genes in the SIRT1/FOXO3 pathway, and lung histopathology were assessed by biochemical and ELISA methods, Real-Time PCR analysis, and H&E staining.Results Curcumin and nanocurcumin produced a remarkable improvement in AlP-induced lung damage through reduction of MDA, induction of antioxidant capacity (TAC, TTG) and antioxidant enzymes (CAT, GPx), modulation of histopathological changes, and up-regulation of genes expression of SIRT1, FOXO3, FOXO1 in lung tissue.Conclusion Nanocurcumin had a significantly more protective effect than curcumin to prevent AlP-induced lung injury via inhibition of oxidative stress. Nanocurcumin could be considered a suitable therapeutic choice for AlP poisoning.
Keywords: Aluminum phosphide; curcumin; nanocurcumin; lung, oxidative stress